JENIS-JENIS BASIDIOMYCOTA DI AREA AIR TERJUN CURUG EMBUN KOTA PAGARALAM DAN SUMBANGANYA PADA PELAJARAN BIOLOGI DI SMA - Efrida Br Sinurat; Endang Dayat; Khoiron Nazip (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2016)
Abstract: A research on the types of Basidiomycota in Area Air Terjun Curug Embun Pagaralam city. The method used is descriptive and sampling conducted with technique cruising. The results showed that in the area there are 20 species distributed into 18 genera, 12 tribes. Types have been found is Polyporus aurcularia, Pycnoporus sanguineus, Earliella scabrosa, Ttrametes elegans, Ganoderma tropicum, Lentinus sajor-caju, Lenzites sp, Lenzites elegans, Mycena chlorohos, Mycena stroobilinoides, Auricularia auricular, Coprinus disseminates, Stereum astrea, Thelophora vialis, Hygrocybe parayensis, Coprrinellus micaceaus, Cyptotrama asprata, Lepiota sp, Clavulina cinerea, Lactarius piperatus.Information on the results of this study can be an alternative example of contextual learning in teaching high school biology class X on the competence of 3.6 Applying Basic Principles for Classifying Mushroom Classification by Characteristics and Reproductive way through thorough and systematic observation. Key Word : Basidiomycota, Curug Embun, Pagaralam